(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2025)
The new behavior of Anagyrus sp.near pseudococci (Girault) on four mealybug hosts was described (Pseudococcus calceolaria, Ps. Viburni, Planococcus ficus, and Pl. Citri (the wasps showed a particular behaviour of host acceptance after antennation. A. sp.nr. pseudocci stayed motionless near the host with her antennae in theupper position for a period of 50 seconds up to about 7.5 minutes, during which the antennae came down gradually. Then the wasp turned back to re-examine the host for no longer than 15 seconds, resuming antennation and ovipositing. In this case oviposition takes more than 50 seconds) and the mean of duration was compared (the mean of duration was Ps.Calceolaria, Pl.Ficus, Pl.Citri, Ps. Viburni 172.8±38.8, 159.9±24.2, 157.4±20.9, 100.4±15.9, Gradually). Also, the host contacts were compared (5.2 ±0.3, 5.1±0.4, 4.4±0.5, 5.5±0.8, Gradually).